Iron-based rare earth boron isotropic nanocomposite magnetic iron alloy, method for producing iron-based rare earth boron isotropic nanocomposite magnetic iron alloy, and method for producing resin-bonded permanent magnet
By adjusting the alloy composition and manufacturing process of iron-based rare earth boron-based isotropic magnet alloys, a nanocomposite magnet alloy with uniform fine metal structure is prepared, which solves the problem that existing materials are difficult to achieve high magnetic characteristics at the same time, and achieves excellent magnetic characteristics of high inherent coercive force, residual magnetic flux density and maximum energy production, which is suitable for electric motors.
Patent Information
- Application Number
- CN202380065895.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-14
- Filing Date
- 2023-06-22
- Publication Date
- 2025-04-22
AI Technical Summary
It is difficult for the existing iron-based rare earth boron-based isotropic magnet materials to achieve excellent magnetic characteristics of high inherent coercive force HcJ, residual magnetic flux density Br and maximum energy product (BH)max at the same time, especially when applied to various electric motors such as EV or HEV.
By adjusting the alloy composition and manufacturing process, an iron-based rare earth boron-based isotropic nanocomposite magnet alloy with uniform fine metal structure is prepared, which specifically includes: a RE2Fe14B type square crystal compound with a concentration of low boron, an average crystal particle size of more than 10 nm and less than 70 nm as the main phase, the grain boundary phase surrounding the main phase contains Fe17RE2 phase or α-Fe phase, and an optimized metal structure is formed through heat treatment processes such as flash annealing.
The magnetic characteristics of high inherent coercive force HcJ≥1200kA/m, residual magnetic flux density Br≥0.81T and maximum energy product (BH)max≥110kJ/m3 are achieved, and are suitable for high-performance electric motors.
Smart Images

Figure CN119866529A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an iron-based rare earth boron isotropic nanocomposite magnet alloy, a method for producing the iron-based rare earth boron isotropic nanocomposite magnet alloy and a method for producing a resin-bonded permanent magnet. Background Art
[0002] In recent years, fine crystalline isotropic magnets composed of hard magnetic phases such as Nd-Fe-B and Sm-Fe-N composed of fine grains with sizes ranging from nanometers to submicrometers, and nanocomposite isotropic magnets (hereinafter referred to as "nanocomposite magnets") have been developed, in which hard magnetic phases such as Nd-Fe-B and Sm-Fe-N composed of fine grains and soft magnetic phases such as Fe-B phase and α-Fe phase exist in the same metal structure. It has been clarified through computer simulation using micromagnetism that these rare earth iron-based isotropic magnets composed of grains with sizes ranging from nanometers to submicrometers have excellent magnetic properties due to their fine grains, which are magnetically coupled to each grain through exchange interaction in addition to static magnetointeraction, and have been put into practical use as high-performance permanent magnet materials.
[0003] Until now, fine crystalline rare earth iron-based isotropic magnets have been crushed to an average particle size of about 50μm to 200μm by utilizing their isotropic properties, and then mixed with epoxy resin-based thermosetting resins or nylon-based and polyphenylene sulfide (PPS) thermoplastic resins to form resin-bonded magnets (commonly known as bonded magnets). These are net shape magnets with high shape freedom, and are mainly used in the electronic component industry represented by optical drives, spindle motors for hard disks, vibration motors (pager motors) for mobile phones, and various sensors. In recent years, due to the high magnetic properties of fine crystalline rare earth iron-based isotropic magnets, they are expected to be developed as brushless DC motors of about 1 horsepower (750W) or less for automobiles (including electric vehicles and hybrid vehicles) and white appliances.
[0004] In particular, in the pursuit of high performance and high efficiency for small motors in the hundreds of watt class, the trend is shifting from brushed motors using existing ferrite magnets to brushless DC motors using bonded magnets. For bonded magnets using fine-crystal rare earth iron-based isotropic magnet materials used in spindle motors, vibration motors, etc., magnet materials with better residual magnetic flux density Br, inherent coercive force HcJ and maximum energy product (BH) max are required.
[0005] In order to meet the requirements of magnetic properties, it is necessary to maximize the volume ratio of the ferromagnetic phase that exhibits hard or soft magnetic properties and minimize the volume ratio of the non-magnetic phase that forms the grain boundary of the hard magnetic phase. 14 The main phase is a B-type (RE is a rare earth element) compound, and there is a non-magnetic grain boundary phase containing boron surrounding the main phase, thereby adjusting the magnetic intercommunication between the main phase particles and obtaining an inherent coercive force HcJ of more than 700 kA / m that can be used in various high-performance motors. 14 The volume ratio of B-type compounds needs to be reduced, and the boron content ratio needs to be reduced. However, when the boron content ratio is reduced too much, the residual magnetic flux density Br and the maximum energy product (BH)max decrease due to the decrease in the squareness of the demagnetization curve. Therefore, there is no practical material that makes the boron content ratio below 0.9 mass%. It is expected that the isotropic rare earth iron boron magnet material with excellent magnetic properties can be achieved by reducing the boron content concentration. In particular, for isotropic rare earth iron boron magnet materials that can be used in various electric motors such as EV or HEV, in order to meet user requirements such as improving heat resistance and miniaturization of motors, it is required that the inherent coercive force HcJ ≥ 1200kA / m, which has been difficult to obtain in isotropic rare earth iron boron magnet materials so far.
[0006] Nd2Fe composed of fine grains can be expected to have high magnetic properties 14 The isotropic magnet with B-type tetragonal compound as the main phase has a basic stoichiometric composition of Nd:Fe:B=11.76:balance:5.88. However, in order to achieve the inherent coercivity HcJ≥1200kA / m that can be applied to various electric motors such as EV or HEV mentioned above, it is necessary to increase RE2Fe 14 The main phase ratio of B requires a concentration of RE greater than RE2Fe 14 The stoichiometric composition of B is high, Nd≥12.5atomic%, but when only the main phase ratio is increased, the residual magnetic flux density Br≥0.8T required to express the magnetic torque of the above-mentioned electric motor is required. When Nd≥12.5atomic%, Fe and B become excess components in the alloy composition, which leads to a decrease in the magnetization of the magnet alloy, so it is impossible to express the maximum energy product (BH)max≥110kJ / m of the rectangularity that can withstand the demagnetization polarity required for obtaining high magnetic torque. 3 , and it is impossible to obtain HcJ ≥ 1200kA / m and Br ≥ 0.81T at the same time.
[0007] In addition, Nd2Fe 14 In the isotropic iron-based rare earth nanocomposite magnet alloy with B-type tetragonal compound as the main phase, Nd2Fe14 The B phase and the α-Fe phase or the Fe-B phase exist in the same metal structure in a nanometer-level crystal grain size, and thus act like a magnet through the exchange interaction between the grains, thus obtaining excellent permanent magnet properties. However, it is impossible to improve the RE2Fe 14 Therefore, no RE-Fe-B based isotropic permanent magnet material showing sufficient magnetic properties has been found.
[0008] Patent Document 1 discloses a method of using RE2Fe 14 B is an anisotropic sintered magnet with a tetragonal crystal structure as the main phase. The magnet is composed of micron-sized RE2Fe 14 B is a metal structure composed of tetragonal crystal grains, and the magnetic moment is oriented in RE2Fe 14 B is a magnet with good magnetic properties because the C-axis of the tetragonal crystal is aligned. However, as an isotropic magnet with randomly arranged magnetic moments, good magnetic properties cannot be obtained and it cannot be used as a practical magnet.
[0009] Patent Document 2 discloses a RE2Fe2O3 composite material composed of at least 10 atomic % of rare earth elements, about 0.5 atomic % to about 10 atomic % of boron, and the remainder of iron. 14 B isotropic permanent magnets with a hard magnetic phase as the main phase of the tetragonal crystal structure have obtained a high intrinsic coercivity HcJ of up to 1460kA / m, but RE2Fe 14 The particle size of B-type grains is 20nm to 400nm, containing more than RE2Fe 14 The single magnetic domain crystal size of the B-type crystal grains is small. As a result, the magnetization decreases. Even in the example with the best magnetic properties, the maximum residual magnetic flux density Br is only 0.83T, and the maximum energy product (BH)max is only 103kJ / m 3 As a result, it is impossible to achieve magnetic characteristics that can be used in various electric motors such as EVs and HEVs.
[0010] Patent Documents 3 and 4 disclose iron-based rare earth isotropic nanocomposite magnets. These iron-based rare earth isotropic nanocomposite magnets mainly contain α-Fe phase as a soft magnetic phase, so it is possible to obtain a high residual flux density Br of 0.9 T or more, but the squareness of the demagnetization curve is poor, and the demagnetization resistance and heat resistance are poor, so they are not suitable as permanent magnet materials used in automobiles and white appliances.
[0011] On the other hand, Patent Document 5 discloses that in an iron-based rare earth isotropic nanocomposite magnet mainly containing an iron-based boride phase as a soft magnetic phase, by adding Ti, the precipitation and growth of the α-Fe phase during the cooling of the alloy melt can be suppressed, and the Nd2Fe14 The precipitation and growth of the B phase proceeds first. However, Ti is easily combined with boron (B), and TiB2 phase is crystallized during the crystallization process, so Nd2Fe 14 There is a problem that the absolute amount of boron required for the formation of the B phase is reduced, and the expected intrinsic coercive force HcJ cannot be obtained according to the content concentration of the rare earth element.
[0012] Patent Document 6 discloses an iron-based rare earth isotropic nanocomposite magnet mainly containing an iron-based boride phase as a soft magnetic phase, and teaches that the following effects are obtained by adding Ti and carbon (C).
[0013] 1. The liquidus temperature of the alloy melt is reduced by more than 5°C (for example, more than about 10°C and less than about 40°C). When the liquidus temperature of the alloy melt is reduced by adding carbon, the crystallization of the coarse TiB2 phase is suppressed even if the alloy melt temperature is reduced accordingly, so the viscosity of the alloy melt hardly increases. As a result, a stable alloy melt flow can be continuously formed during the quenching process of the alloy melt.
[0014] 2. If the alloy melt temperature is lowered, sufficient cooling can be achieved on the surface of the cooling roll, thereby preventing winding on the cooling roll and making the structure of the rapidly solidified alloy uniformly refined.
[0015] 3. Due to the high concentration of (B+C) and high amorphous forming ability, it is easy to obtain fine metal structure even if the alloy melt is cooled at a low rate of about 100℃ / sec to 10000℃ / sec. Therefore, it is possible to produce Nd2Fe with a volume ratio of more than 60% without precipitating coarse α-Fe phase. 14 B phase of the quenched alloy.
[0016] As described above, it is believed that in the iron-based rare earth isotropic nanocomposite magnet described in Patent Document 6, which requires the addition of Ti, the uniform and fine Nd2Fe 14 The hard magnetic phase of the B-type crystal structure and the soft magnetic phase composed of the Fe phase and the Fe-B phase coexist in the same metal structure, thereby obtaining excellent permanent magnet properties. However, Ti, which is an essential element, is a non-magnetic element and does not enter Nd2Fe as a compound. 14 The B phase, Fe phase, and Fe-B phase are dispersed in the grain boundaries, resulting in a decrease in magnetization, and it is impossible to achieve magnetic properties that can be used in various electric motors such as EVs and HEVs.
[0017] Prior art literature
[0018] Patent Literature
[0019] Patent Document 1: Japanese Patent Application Laid-Open No. 59-46008
[0020] Patent Document 2: Japanese Patent Application Laid-Open No. 60-9852
[0021] Patent Document 3: Japanese Patent Application Laid-Open No. 8-162312
[0022] Patent Document 4: Japanese Patent Application Laid-Open No. 10-53844
[0023] Patent Document 5: Japanese Patent Application Publication No. 2002-175908
[0024] Patent Document 6: Japanese Patent Application Publication No. 2003-178908 Summary of the invention
[0025] In order to be applicable to various electric motors such as EV and HEV, the inherent coercivity HcJ ≥ 1200 kA / m is required, and the maximum energy product (BH) max ≥ 110 kJ / m is required to obtain the required minimum magnetic torque and obtain an excellent squareness of the demagnetization curve. 3 In order to achieve a residual magnetic flux density Br ≥ 0.81T, it is necessary to suppress non-magnetic additive elements such as Ti that do not form compounds, and to maximize the interaction between particles, the grain size is miniaturized to an average crystal grain size of more than 10nm and less than 70nm so that the exchange interaction can be effectively exerted, and at the same time, the interaction between particles is adjusted to maximize the coercive force. There is such a problem.
[0026] In addition, the inherent coercivity HcJ and the residual magnetic flux density Br are in a trade-off relationship. In order to increase the inherent coercivity HcJ, the increase in the magnetic flux density by RE2Fe 14 When the volume ratio of the main phase composed of B-type hard magnetic compounds is reduced, the residual magnetic flux density Br decreases. Therefore, in order to suppress the decrease of the residual magnetic flux density Br, in addition to increasing the exchange interaction between the particles by using the above-mentioned uniform and fine metal organization, it is also necessary to make the grain boundary phase adjacent to the main phase highly magnetized and have a certain degree of anisotropic magnetic field. Hard magnetic or semi-hard magnetic phase.
[0027] The present inventors considered whether it is possible to 14 The main adjacent grain boundary phase composed of B-type hard magnetic compounds is hard magnetic or semi-hard magnetic to obtain a permanent magnet material with excellent magnetic properties that have never been seen before. However, as mentioned above, it is known that added elements such as Ti make it difficult to suppress the decrease in residual magnetic flux density Br while maintaining a high inherent coercive force HcJ.
[0028] The present invention is made in view of the above situation, and its main purpose is to provide an iron-based rare earth boron isotropic nanocomposite magnet alloy that can ensure the magnet alloy properties required for various electric motors such as EV or HEV, and can improve the residual magnetic flux density, inherent coercive force HcJ and maximum energy product (BH)max compared to the existing iron-based rare earth boron isotropic magnet alloys, a method for manufacturing the above-mentioned iron-based rare earth boron isotropic nanocomposite magnet alloy, and a method for manufacturing a resin-bonded permanent magnet of the above-mentioned iron-based rare earth boron isotropic nanocomposite magnet alloy.
[0029] The iron-based rare earth boron isotropic nanocomposite magnet alloy of the present invention has the following alloy composition: having a composition formula T 100-x-y-z (B 1-n C n ) x RE y Zr z M m (T is at least one element selected from Fe, Co and Ni and is a transition metal element that must contain Fe, RE is at least one rare earth element selected from Nd and Pr and must contain Nd, and M is one or more metal elements selected from Al, Si, V, Cr, Ti, Mn, Cu, Zn, Ga, Nb, Mo, Ag, Hf, Ta, W, Pt, Au and Pb), and the composition ratios x, y and z respectively satisfy 4.2 atomic % ≤ x ≤ 5.0 atomic %, 12.5 atomic % ≤ y ≤ 14.0 atomic %, 0 atomic % < z ≤ 2.0 atomic %, 0.0 atomic % ≤ m ≤ 5.0 atomic % and 0.0 ≤ n ≤ 0.5; and has the following metal structure: B contains a concentration lower than RE2Fe 14 The stoichiometric composition of the B-type tetragonal compound is RE2Fe with an average crystal particle size of 10 nm or more and less than 70 nm, which is finer than the single magnetic domain critical diameter. 14 The main phase is a tetragonal compound of type B, and the grain boundary phase surrounding the main phase contains Fe 17 RE2 phase or α-Fe phase is a phase richer in Fe than the main phase.
[0030] In the iron-based rare earth boron isotropic nanocomposite magnet alloy, the width of the thickest part of the grain boundary phase can be greater than 1 nm and less than 150 nm. In addition, the metal structure can have a ratio of the main phase to the grain boundary phase of 70 volume % or more and less than 99 volume % and a ratio of the grain boundary phase of 1 volume % or more and less than 30 volume %.
[0031] The method for producing an isotropic iron-based rare earth boron-based nanocomposite magnet alloy of the present invention comprises the following steps: a step of preparing an alloy melt having the following composition, namely, 100-x-y-z(B 1-n C n ) x RE y Zr z M m (T is at least one element selected from Fe, Co and Ni and is a transition metal element that must contain Fe, RE is at least one rare earth element that must contain Nd among Nd and Pr, and M is at least one metal element selected from Al, Si, V, Cr, Ti, Mn, Cu, Zn, Ga, Nb, Mo, Ag, Hf, Ta, W, Pt, Au and Pb), and the composition ratios x, y and z satisfy 4.2 atomic % ≤ x ≤ 5.0 atomic %, 12.5 atomic % and 12.5 atomic % respectively. atom % ≤ y ≤ 14.0 atom %, 0 atom % < z ≤ 2.0 atom %, 0.0 atom % ≤ m ≤ 5.0 atom % and 0.0 ≤ n ≤ 0.5; and, the alloy melt is ejected onto the surface of a rotating roller mainly composed of Cu, Mo, W or an alloy containing at least one of these metals at an average discharge rate of 200 g / min or more and less than 2000 g / min per one of the orifices arranged at the front end of the nozzle, thereby producing a molten alloy having 1 volume % or more and containing RE2Fe 14 A step of rapidly solidifying the alloy by quenching any one of the crystalline phase and the amorphous phase of the B phase.
[0032] The manufacturing method of the above-mentioned resin-bonded permanent magnet may include the following steps: a step of preparing an iron-based rare earth boron isotropic nanocomposite magnet alloy powder manufactured by the above-mentioned method of manufacturing an iron-based rare earth boron isotropic nanocomposite magnet alloy, and a step of adding a thermosetting resin to the above-mentioned iron-based rare earth boron isotropic nanocomposite magnet alloy powder, filling it into a molding mold, and performing heat treatment at a temperature above the polymerization temperature of the above-mentioned thermosetting resin after forming a compression molded body through compression molding.
[0033] The manufacturing method of the above-mentioned resin-bonded permanent magnet may include the following steps: a step of preparing iron-based rare earth boron isotropic nanocomposite magnet alloy powder manufactured by the above-mentioned method of manufacturing iron-based rare earth boron isotropic nanocomposite magnet alloy, and a step of adding thermoplastic resin to the above-mentioned iron-based rare earth boron isotropic nanocomposite magnet alloy powder to prepare a composite material for injection molding, and then performing injection molding.
[0034] According to the present invention, a rare earth boron isotropic nanocomposite magnet alloy can be provided that can ensure the magnetic properties such as residual magnetic flux density Br, inherent coercive force HcJ, maximum energy product (BH)max, etc. required as a permanent magnet for various electric motors such as EV or HEV. In addition, according to the present invention, a method for manufacturing the above-mentioned rare earth boron isotropic nanocomposite magnet alloy can be provided. In addition, according to the present invention, a method for manufacturing a resin-bonded permanent magnet containing the above-mentioned rare earth boron isotropic nanocomposite magnet alloy can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a cross-sectional view schematically showing an example of the iron-based rare earth boron-based isotropic magnet alloy of the present invention.
[0036] Figure 2 (a) is a diagram showing the structure of a heat treatment furnace for flash annealing. Figure 2 (b) is a diagram showing the state of the rapidly solidified alloy moving inside the furnace tube.
[0037] Figure 3 This is a conceptual diagram of the thermal history of flash annealing performed in the present invention.
[0038] Figure 4 This is the powder X-ray diffraction pattern of the rapidly solidified alloy obtained in Example 9.
[0039] Figure 5 This is a powder X-ray diffraction pattern of the rapidly solidified alloy obtained in Example 9 after flash annealing (crystallization heat treatment).
[0040] Figure 6 This is the element mapping image obtained in Example 24.
[0041] Figure 7 This is a powder X-ray diffraction pattern of the rapidly solidified alloy obtained in Comparative Example 7 after flash annealing (crystallization heat treatment). DETAILED DESCRIPTION
[0042] The following describes the rare earth boron isotropic nanocomposite magnet alloy of the present invention, the method for manufacturing the rare earth boron isotropic nanocomposite magnet alloy of the present invention, the method for manufacturing the powder composed of the rare earth boron isotropic nanocomposite magnet alloy of the present invention, and the method for manufacturing the resin-bonded permanent magnet of the present invention. It should be noted that the present invention is not limited to the following configurations and can be appropriately changed within the scope of the present invention. In addition, the configuration obtained by combining multiple of the preferred configurations described below also belongs to the present invention.
[0043] The rare earth boron isotropic nanocomposite magnet alloy of the present invention has the following alloy composition: having a composition formula T 100-x-y-z (B1-n C n ) x RE y Zr z M m (T is at least one element selected from Fe, Co and Ni and is a transition metal element that must contain Fe, RE is at least one rare earth element selected from Nd and Pr and must contain Nd, and M is one or more metal elements selected from Al, Si, V, Cr, Ti, Mn, Cu, Zn, Ga, Nb, Mo, Ag, Hf, Ta, W, Pt, Au and Pb), and the composition ratios x, y and z respectively satisfy 4.2 atomic % ≤ x ≤ 5.0 atomic %, 12.5 atomic % ≤ y ≤ 14.0 atomic %, 0 atomic % < z ≤ 2.0 atomic %, 0.0 atomic % ≤ m ≤ 5.0 atomic % and 0.0 ≤ n ≤ 0.5; and has the following metal structure: B contains a concentration lower than RE2Fe 14 The stoichiometric composition of the B-type tetragonal compound and the RE2Fe2O3 having an average crystal particle size of 10 nm or more and less than 70 nm which is finer than the single magnetic domain critical diameter 14 The main phase is a tetragonal compound of type B, and the grain boundary phase surrounding the main phase contains Fe 17 RE2 phase or α-Fe phase is a phase richer in Fe than the main phase.
[0044] The width of the thickest part of the grain boundary phase is preferably 1 nm or more and less than 150 nm. An example of such an iron-based rare earth boron-based isotropic magnet alloy of the present invention is shown in FIG. Figure 1 .
[0045] In the composition ratio of the main phase to the grain boundary phase, it is preferred that the ratio of the main phase is 70 volume % or more and less than 99 volume % and the ratio of the grain boundary phase is 1 volume % or more and less than 30 volume %, but it is not necessarily limited thereto.
[0046] The rare earth boron isotropic nanocomposite magnet alloy of the present invention is characterized by low boron concentration, so that RE2Fe 14 The boron (B) content of the alloy composition range of the magnet alloy with B phase as the main phase is about 2.5% of RE2Fe 14 The stoichiometric composition of the B-type tetragonal compound is low, and the range of 4.2 atomic % or more and less than 5.0 atomic % must be included, and Zr must be included in the range of 2.0 atomic % or less. In addition, in the rare earth boron isotropic nanocomposite magnet alloy of the present invention, the rare earth element (RE) and iron (Fe) are in excess in the same alloy structure, thereby forming RE2Fe2O3 as the main phase. 14The formation of B phase is unnecessary for the grain boundary phase composed of excess RE and Fe. Therefore, the iron-based rare earth boron isotropic magnet alloy of the present invention can have a unique fine metal structure, that is, there are RE2Fe2O3 surrounding the average crystal grain size of 10nm or more and less than 70nm. 14 B phase, containing Fe 17 A phase richer in Fe than the main phase, such as the RE2 phase or the α-Fe phase, and a grain boundary phase whose thickest portion has a width of 1 nm or more and less than 150 nm.
[0047] The inventors of the present invention believe that by realizing the above-mentioned unique uniform and fine metal structure, RE2Fe 14 The B phase and the grain boundary phase composed mainly of RE and Fe uniformly present around the main phase are bonded by strong exchange interaction in addition to static magnetointeraction. However, if the exchange interaction (exchange bonding) becomes stronger, the intrinsic coercivity HcJ of the magnet alloy will decrease. However, it was found that by adjusting the RE-Fe-B combination and the Zr addition concentration, the existence of Fe 17 The unique metal structure of the grain boundary phase, which is richer in Fe than the main phase, such as RE2 phase or α-Fe phase, can suppress RE2Fe 14 The HcJ of the B phase is reduced, and a residual magnetic flux density Br that can be applied to various electric motors such as EVs and HEVs and a high maximum energy product (BH)max due to the improved squareness of the demagnetization curve can be obtained. In particular, by adopting the above-mentioned metal structure, a high HcJ that cannot be achieved by the existing rare earth iron boron isotropic magnet can be obtained without adding extremely rare and effective heavy rare earth elements such as Dy and Tb.
[0048] When the boron content is less than 4.2 atomic %, the RE2Fe 14 The formation of B phase causes the intrinsic coercivity HcJ and residual magnetic flux density Br to decrease significantly. In addition, when the boron concentration is greater than 5.0 atomic %, Fe is not precipitated in the grain boundary phase. 17 RE2 phase or α-Fe phase is richer in Fe than the main phase. Therefore, although the residual magnetic flux density Br can be achieved above 0.81T, it is impossible to maintain the maximum energy product (BH) max: 110kJ / m 3 At the same time, the intrinsic coercive force HcJ is obtained: 1200kA / m or more.
[0049] In contrast, it is believed that by setting the boron content to 4.2 atomic % to 5.0 atomic %, the RE2Fe required to obtain an intrinsic coercive force HcJ ≥ 1200 kA / m or more can be obtained without damaging the RE2Fe 14 In the case of the formation of B phase, a uniform Fe-containing 17Since the RE2 phase or the α-Fe phase is a grain boundary phase richer in Fe than the main phase and contains RE and Fe as main components, the above-mentioned magnetic properties can be obtained.
[0050] Patent Documents 2, 3, 4, 5 and 6 all disclose RE2Fe 14 B-type tetragonal compound is responsible for the intrinsic coercivity HcJ of the microcrystalline isotropic permanent magnet material, but the size of the intrinsic coercivity HcJ depends largely on RE2Fe 14 Volume ratio of B-type tetragonal compound, RE2Fe 14 The higher the volume ratio of the B phase, the higher the intrinsic coercivity HcJ, and the higher the RE2Fe 14 The lower the volume ratio of the B phase, the lower the intrinsic coercive force HcJ.
[0051] On the other hand, the anisotropic RE2Fe 14 In the B sintered magnet, RE2Fe 14 B-type tetragonal compounds contain heavy rare earth elements such as Dy and Tb, which can increase the RE2Fe 14 The anisotropic magnetic field of the B-type tetragonal compound is improved to achieve the improvement of the intrinsic coercive force HcJ. 14 The B-type tetragonal compound is the main phase, but the main phase size of the anisotropic sintered magnet is about 1μm to 10μm, which is RE2Fe 14 Therefore, the anisotropic sintered magnet is in a multi-domain state before magnetization, and the magnetic moments are aligned in the magnetization direction (C-axis direction) by magnetization, becoming a single domain state, showing permanent magnet characteristics. Therefore, the intrinsic coercive force HcJ of the anisotropic sintered magnet represents the ability to keep the magnetic moments aligned in the same direction. Therefore, by increasing RE2Fe 14 The anisotropic magnetic field of the B-type tetragonal compound increases, thereby increasing the intrinsic coercive force HcJ.
[0052] It is found that the low-boron-containing iron-based rare earth boron-based isotropic nanocomposite magnet alloy of the present invention makes the metal structure of the magnet alloy uniformly refined by adding Zr within a certain range, and obtains an excellent rectangularity of the demagnetization curve by optimizing the exchange bonding between particles, and can realize the composition ratio and metal structure change of each phase contained in the alloy, and has the advantages of containing Fe 17 The unique metal structure of the grain boundary phase, which is a phase richer in Fe than the main phase, such as RE2 or α-Fe phase, is obtained. 14 The intrinsic coercivity HcJ of B-type tetragonal compounds decreases, and RE2Fe14 An isotropic nanocomposite magnet having a B-type tetragonal compound as a main phase and a ferromagnetic compound composed of Fe and B containing a phase richer in Fe than the main phase as a subphase. As a result, the iron-based rare earth boron-based isotropic nanocomposite magnet of the present invention can suppress a significant decrease in the residual magnetic flux density Br, and at the same time, obtain a high intrinsic coercivity HcJ that cannot be achieved by the existing iron-based rare earth boron-based isotropic magnets without adding heavy rare earths such as Dy and Tb.
[0053] In addition, it was found that the iron-based rare earth boron isotropic nanocomposite magnet alloy of the present invention, which is characterized by a low boron content concentration, achieves an increase in the inherent coercive force HcJ without causing a decrease in the residual magnetic flux density Br by replacing a portion of the boron (B) with carbon (C), and that the effect of improving the inherent coercive force HcJ can be increased by combining carbon (C) substitution with the addition of heavy rare earth elements.
[0054] [Alloy composition]
[0055] The alloy composition of the iron-based rare earth boron isotropic nanocomposite magnet alloy of the present invention has the following composition: 100-x-y-z (B 1-n C n ) x RE y Zr z M m (T is at least one element selected from Fe, Co and Ni and is a transition metal element that must contain Fe, RE is at least one rare earth element that must contain Nd among Nd and Pr, and M is one or more metal elements selected from Al, Si, V, Cr, Ti, Mn, Cu, Zn, Ga, Nb, Mo, Ag, Hf, Ta, W, Pt, Au and Pb), and the composition ratios x, y and z respectively satisfy 4.2 atomic % ≤ x ≤ 5.0 atomic %, 12.5 atomic % ≤ y ≤ 14.0 atomic %, 0 atomic % < z ≤ 2.0 atomic %, 0.0 atomic % ≤ m ≤ 5.0 atomic % and 0.0 ≤ n ≤ 0.5. It should be noted that the composition of the entire magnet alloy involved in the present invention is analyzed using ICP mass spectrometry or fluorescent X-ray analysis. In addition, combustion-infrared absorption method can be used in combination as needed.
[0056] The transition metal element T containing Fe as an essential element accounts for the balance of the above-mentioned elements. Even if a part of Fe is replaced with one or two of Co and Ni, which are also ferromagnetic elements like Fe, the desired hard magnetic properties can be obtained. However, when the replacement amount of Fe exceeds 30%, it leads to a significant decrease in the magnetic flux density, so the preferred replacement amount is in the range of 0% to 30%. It should be noted that the addition of Co not only helps to improve the magnetization, but also reduces the viscosity of the alloy melt and is effective in stabilizing the discharge rate from the nozzle when the alloy melt is quenched. The more preferred Co replacement amount is 0.5% to 30%. From the perspective of cost-effectiveness, the more preferred Co replacement amount is 0.5% to 10%.
[0057] In the iron-based rare earth boron isotropic nanocomposite magnet alloy of the present invention, if the composition ratio x of B+C is less than 4.2 atomic %, it is impossible to ensure RE2Fe 14 The amount of B+C required for the formation of B-type tetragonal compounds leads to a decrease in magnetic properties and a significant decrease in amorphous forming ability, so that the α-Fe phase precipitates when the alloy melt is rapidly cooled and solidified, resulting in the loss of the squareness of the demagnetization curve. In addition, if the composition ratio x of B+C exceeds 5.0 atomic %, it is impossible to form a tetragonal compound containing Fe. 17 The RE2 phase or α-Fe phase, which is a phase richer in Fe than the main phase, is a grain boundary phase with RE and Fe as main components, and the intrinsic coercivity HcJ decreases, so the above-mentioned magnetic properties may not be ensured. Therefore, the composition ratio x is limited to the range of 4.2 atomic % to 5.0 atomic %. The composition ratio x is preferably 4.4 atomic % to 4.9 atomic %, and more preferably 4.5 atomic % to 4.9 atomic %.
[0058] In the iron-based rare earth boron isotropic nanocomposite magnet alloy of the present invention, by replacing a part of B with C, the melting point of the alloy melt is lowered, and the loss of refractory used during rapid solidification is reduced, so the process cost of rapid solidification can be reduced, and the effect of improving the inherent coercive force HcJ can be obtained. However, when the substitution rate of C to B exceeds 50%, the amorphous forming ability is greatly reduced, so it is not preferred. Therefore, the substitution rate of C to B is limited to the range of 0% to 50%, that is, 0.0≤n≤0.5. It should be noted that from the perspective of the effect of improving the inherent coercive force HcJ, the substitution rate of C to B is preferably 2% to 30%, and more preferably 3% to 15%.
[0059] In the iron-based rare earth boron-based isotropic nanocomposite magnet alloy of the present invention, if the composition ratio y of at least one rare earth element RE, which must contain at least Nd among Nd and Pr, is less than 12.5 atomic %, it is impossible to generate a rare earth element containing Fe. 17The grain boundary phase with RE and Fe as the main components, which is a phase richer in Fe than the main phase, such as RE2 phase or α-Fe phase, may not ensure the above-mentioned magnetic properties. In addition, if the composition ratio y is greater than 14.0 atomic %, the magnetization decreases significantly. Therefore, the composition ratio y is limited to the range of 12.5 atomic % to 14.0 atomic %. In addition, from the perspective of ensuring the stability of the inherent coercive force HcJ, the composition ratio y is preferably 12.6 atomic % to 14.0 atomic %, and from the perspective of ensuring a high residual magnetic flux density Br, it is more preferably 12.8 atomic % to 13.5 atomic %.
[0060] In addition, the rare earth element RE mentioned above can be RE y =(Nd 1-l Pr l ) y , at this time, l is limited to 0.05 to 0.7. It should be noted that if the ratio l of Pr to Nd is too low, the effect of improving HcJ is small. In addition, if l is too high, the absolute value of the temperature coefficient β related to the coercive force of the magnet alloy becomes small, and there is a concern about the decrease in heat resistance. Therefore, l is preferably 0.15 to 0.6, and more preferably 0.2 to 0.5.
[0061] In the iron-based rare earth boron-based isotropic nanocomposite magnet alloy of the present invention, Zr is an additive element necessary for the uniform refinement of the magnet alloy and the formation of a phase richer in Fe than the main phase at the grain boundary. If the composition ratio z of Zr is greater than 2.0 atomic %, it will lead to a decrease in magnetization and a residual magnetic flux density Br of more than 0.81 T cannot be obtained. Therefore, the composition ratio z is limited to a range of less than 2.0 atomic %. In addition, from the perspective of improving the rectangularity of the demagnetization curve, the composition ratio z is preferably 0.6 atomic % to 2.0 atomic %, and from the perspective of ensuring a high residual magnetic flux density Br, it is more preferably 0.7 atomic % to 1.5 atomic %.
[0062] In the iron-based rare earth boron isotropic magnet alloy of the present invention, one or more metal elements M selected from Al, Si, V, Cr, Ti, Mn, Cu, Zn, Ga, Nb, Mo, Ag, Hf, Ta, W, Pt, Au and Pb can be added. By adding the metal element M, the amorphous forming ability is improved, the inherent coercive force HcJ is improved due to the uniform refinement of the metal structure after the crystallization heat treatment, the squareness of the demagnetization curve is improved, and the magnetic properties are improved. However, if the composition ratio m of these metal elements M exceeds 5.0 atomic%, it will lead to a decrease in magnetization, so the composition ratio m is limited to the range of 0.0 atomic% to 5.0 atomic%. In addition, the composition ratio m is preferably 0.0 atomic% to 3.0 atomic%, and more preferably 0.0 atomic% to 2.0 atomic%.
[0063] [Metallic structure]
[0064] In the iron-based rare earth boron isotropic nanocomposite magnet alloy of the present invention, if RE2Fe 14 If the average crystal grain size of the B-type tetragonal compound is less than 10nm, the intrinsic coercivity HcJ decreases. If it is greater than 70nm, the squareness of the demagnetization curve decreases due to the decrease in the exchange interaction between the crystal particles. Therefore, in order to achieve a residual magnetic flux density Br of more than 0.81T, an intrinsic coercivity HcJ of more than 1200kA / m and less than 1700kA / m, and a maximum energy product (BH) max of 110kJ / m 3 The above magnetic properties will RE2Fe 14 The average crystal particle size of the B-type tetragonal compound is limited to a range of 10 nm or more and less than 70 nm. 14 The average crystal particle size of the B-type tetragonal compound is preferably 15 nm to 60 nm, more preferably 15 nm to 50 nm.
[0065] RE2Fe 14 The average crystal particle size of the B-type tetragonal compound refers to the average value of the circle-equivalent diameters of particles existing in the field of view when the particle sizes of particles at three or more locations are measured by the line segment method using a transmission electron microscope (TEM).
[0066] It should be noted that the above-mentioned RE2Fe 14 The main phase is composed of a B-type tetragonal compound, containing Fe 17 When the width of the grain boundary phase with RE and Fe as the main components of the phase richer in Fe than the main phase, such as the RE2 phase or the α-Fe phase, is less than 1 nm, the binding force between the main phase particles is enhanced, resulting in a decrease in the inherent coercive force HcJ. In addition, if the width of the thickest part of the grain boundary phase is greater than 150 nm, the binding between the particles becomes weaker, and the rectangularity of the demagnetization curve decreases. Therefore, the width of the thickest part of the grain boundary phase is preferably greater than 1 nm and less than 150 nm, more preferably 2 nm to 100 nm, and further preferably 2 nm to 10 nm, but it is not necessarily limited to this. It should be noted that the width of the grain boundary phase is obtained by image analysis of a bright field image taken using a scanning transmission electron microscope under the conditions of an acceleration voltage of 200 kV and an observation magnification of 900,000 times.
[0067] In the iron-based rare earth boron-based isotropic nanocomposite magnet alloy of the present invention, in the composition ratio of the main phase and the grain boundary phase, the ratio of the main phase is preferably 70 volume % or more and less than 99 volume %, and the ratio of the grain boundary phase is 1 volume % or more and less than 30 volume %. As a result, it is easy to achieve a residual magnetic flux density Br of 0.81T or more, an inherent coercive force HcJ of 1200kA / m or more and less than 1700kA / m, and a maximum energy product (BH)max of 110kJ / m 3 It should be noted that the main phase ratio is preferably 80 volume % or more and less than 99 volume %, and more preferably 90 volume % or more and less than 98 volume %. It should be noted that the composition ratio of the main phase to the grain boundary phase is obtained by image analysis of a bright field image taken using a scanning transmission electron microscope at an acceleration voltage of 200 kV and an observation magnification of 900,000 times.
[0068] [Magnetic properties]
[0069] The iron-based rare earth boron isotropic nanocomposite magnet alloy of the present invention is as follows, which can ensure that the residual flux density Br is above 0.81T and the maximum energy product (BH)max is 110kJ / m 3 The above, and the inherent coercive force HcJ is 1200kA / m or more and less than 1700kA / m, which has been impossible to achieve as an iron-based rare earth boron isotropic magnet alloy so far. As the permanent magnet characteristics of the existing iron-based rare earth boron isotropic magnet with an inherent coercive force HcJ of less than 1200kA / m, it is difficult to apply to various electric motors such as EV or HEV that are small and require high heat resistance, so the inherent coercive force HcJ is preferably 1200kA / m or more, and more preferably 1250kA / m or more. It should be noted that when the inherent coercive force HcJ is more than 1700kA / m, the magnetization is significantly reduced, so the inherent coercive force HcJ is preferably 1700kA / m or less, and more preferably 1600kA / m or less. In addition, for the residual magnetic flux density Br, when using an iron embedded rotor (IPM type rotor), in order to be able to drive at a higher operating point (magnetic permeability) than the SPM type, the residual magnetic flux density Br should be as high as possible. However, considering the balance between heat resistance and inherent coercive force HcJ, the residual magnetic flux density Br is preferably above 0.81T, and more preferably above 0.82T.
[0070] It should be noted that the reason for making the residual magnetic flux density Br greater than 0.81T is as follows: When the isotropic bonded magnet is used in a DC brushless motor, the working point (magnetic permeability Pc) of the magnet is about 3 to 10. Therefore, if the residual magnetic flux density Br ≥ 0.81T, the maximum energy product (BH) max of 300kJ / m is obtained within the Pc range. 3The above anisotropic Nd-Fe-B sintered magnet has an effective magnetic flux Bm at 120° C. of the same level as Bm. It should be noted that the residual magnetic flux density Br is more preferably 0.82T or more.
[0071] In addition, the reason for making the inherent coercive force HcJ greater than 1200 kA / m is as follows: When the inherent coercive force HcJ is less than 1200 kA / m, when it is applied to a DC brushless motor as an isotropic bonded magnet, the heat resistance temperature of the motor cannot be ensured to be 120°C, and the required motor characteristics may not be obtained due to thermal demagnetization. In addition, the reason for making the inherent coercive force HcJ less than 1700 kA / m is as follows: When the inherent coercive force HcJ is greater than 1700 kA / m, the magnetization is greatly reduced, and in a magnet style with a long magnetic path such as polar anisotropic magnetization, the magnetic path is not connected, and the required effective magnetic flux Bm cannot be obtained.
[0072] In addition, the maximum energy product (BH) is set to 110 kJ / m 3 The reasons for the above are as follows: The maximum energy product (BH)max is less than 110kJ / m 3 When the squareness ratio of the demagnetization curve (residual magnetization Jr / saturation magnetization Js) becomes less than 0.8, when it is used as an isotropic bonded magnet in a DC brushless motor, the magnetic properties will deteriorate due to the reverse magnetic field generated when the motor is working, and the desired motor characteristics may not be obtained.
[0073] The method for producing an isotropic iron-based rare earth boron-based nanocomposite magnet alloy according to the present invention is characterized in that it comprises the following steps: a step of preparing an alloy melt having the following composition, namely, a composition formula T 100-x-y-z (B 1-n C n ) x RE y Zr z M m(T is at least one element selected from Fe, Co and Ni and is a transition metal element that must contain Fe, RE is at least one rare earth element that must contain Nd among Nd and Pr, and M is at least one metal element selected from Al, Si, V, Cr, Ti, Mn, Cu, Zn, Ga, Nb, Mo, Ag, Hf, Ta, W, Pt, Au and Pb), and the composition ratios x, y and z respectively satisfy 4.2 atomic % ≤ x ≤ 5.0 atomic %, 12. 5 atomic % ≤ y ≤ 14.0 atomic %, 0 atomic % < z ≤ 2.0 atomic %, 0.0 atomic % ≤ m ≤ 5.0 atomic % and 0.0 ≤ n ≤ 0.5; and ejecting the alloy melt onto the surface of a rotating roller mainly composed of Cu, Mo, W or an alloy containing at least one of these metals at an average discharge rate of 200 g / min or more and less than 2000 g / min per one of the orifices arranged at the front end of the nozzle, thereby producing a RE2Fe alloy having 1 volume % or more. 14 A step of rapidly solidifying the alloy of any one of the crystalline phase and the amorphous phase of the B phase. It should be noted that RE is at least one rare earth element substantially free of La and Ce, and as an example, it can be at least one rare earth element of Nd and Pr that must contain at least Nd. The details are as described above.
[0074] [Quick cooling of alloy melt]
[0075] In the method for producing an isotropic iron-based rare earth boron-based nanocomposite magnet alloy of the present invention, raw materials prepared to form a predetermined alloy composition are melted to form an alloy melt, and then the alloy melt is ejected onto the surface of a rotating roller mainly composed of Cu, Mo, W or an alloy containing at least one of these metals at an average discharge rate of 200 g / min or more and less than 2000 g / min per orifice arranged at the front end of the nozzle, thereby producing a magnet having a content of 1% by volume or more of RE2Fe 14 If the average discharge rate of the quenched solidified alloy of any one of the crystalline phase and the amorphous phase of the B phase is less than 200g / min, the productivity is poor. When it is more than 2000g / min, the alloy melt containing a coarse α-Fe phase is quenched alloy structure, so even if the crystallization heat treatment is performed, the above-mentioned magnetic properties may not be obtained. Therefore, the average discharge rate of each orifice arranged at the front end of the nozzle is limited to a range of more than 200g / min and less than 2000g / min. It should be noted that the average discharge rate is preferably 300g / min to 1500g / min, and more preferably 400g / min to 1300g / min.
[0076] The hole for discharging the alloy melt arranged at the front end of the nozzle may not be a circular orifice, and may be a square, triangle, ellipse, or other shape as long as the hole shape can ensure the prescribed discharge rate, and a slit shape is also allowed. In addition, the nozzle material is allowed as long as it is a refractory material that does not react or is difficult to react with the alloy melt, but it is preferred to use a ceramic material, SiC, C or BN that has little loss to the nozzle hole by the alloy melt being discharged, and BN is more preferred, and hard BN containing additives is further preferred.
[0077] When making the above-mentioned quench solidification alloy, by preventing the oxidation of the alloy melt and suppressing the increase of the viscosity of the alloy melt, a stable discharge rate can be maintained, so the quench solidification atmosphere is preferably an oxygen-free or low-oxygen atmosphere. In order to achieve this atmosphere, it is necessary to evacuate the quench solidification device to below 20Pa, preferably below 10Pa, and more preferably below 1Pa, and then introduce an inert gas into the quench solidification device, so that the oxygen concentration in the quench solidification device is below 500ppm, preferably below 200ppm, and more preferably below 100ppm, and then quench solidification is implemented. As an inert gas, rare gases such as helium and argon, and nitrogen can be used, but nitrogen is easier to react with rare earth elements and iron, so rare gases such as helium and argon are preferred, and argon is more preferred from a cost perspective.
[0078] In the process of making a quenching solidified alloy, the rotating roller that quenches the alloy melt has Cu, Mo, W or an alloy containing at least one of these metals as the main component, but it is preferred to have a substrate containing such a main component. This is because these substrates have excellent thermal conductivity and durability. In addition, by plating Cr, Ni or a combination of them on the surface of the substrate of the rotating roller, the heat resistance and hardness of the substrate surface of the rotating roller can be improved, and the melting and degradation of the substrate surface of the rotating roller during quenching solidification can be suppressed. It should be noted that the diameter of the rotating roller is, for example, Φ200mm to Φ20000mm. As long as the quenching solidification time is a short time of less than 10 seconds, there is no need to water-cool the rotating roller. When the quenching solidification time exceeds 10 seconds, it is preferred to flow cooling water inside the rotating roller to suppress the temperature rise of the rotating roller substrate. The water cooling capacity of the rotating roller is preferably calculated based on the solidification latent heat per unit time and the discharge rate, and appropriately optimized and adjusted.
[0079] [Flash annealing]
[0080] The method for manufacturing an isotropic nanocomposite magnet alloy of an iron-based rare earth boron system of the present invention preferably further comprises a step of performing flash annealing, that is, after the above-mentioned rapidly cooled solidified alloy reaches a certain temperature range above the crystallization temperature and below 850°C at a heating rate of 10°C / second or more and less than 200°C / second, it is rapidly cooled after 0.1 second or more and less than 7 minutes, and by performing the above-mentioned flash annealing, the following metal structure is formed: B contains a concentration lower than RE2Fe14 The stoichiometric composition of the B-type tetragonal compound is RE2Fe with an average crystal particle size of 10 nm or more and less than 70 nm. 14 The main phase is a tetragonal compound of type B, and there is a Fe-containing 17 The RE2 phase has a grain boundary phase with a width of 1 nm or more and less than 10 nm, and is larger than RE2Fe 14 The single magnetic domain critical diameter of B-type tetragonal compounds is very small.
[0081] When the heating rate during flash annealing (crystallization heat treatment) is less than 10°C / sec, the grains grow excessively and a fine metal structure cannot be obtained, resulting in a decrease in the inherent coercive force HcJ and residual magnetic flux density Br. When the heating rate is more than 200°C / sec, the grains do not grow in time and will not become RE2Fe with an average crystal grain size of more than 10nm and less than 70nm required for the performance of permanent magnets. 14 The main phase is a tetragonal compound of type B, and a grain boundary phase with a width of 1 nm or more and less than 10 nm and mainly composed of RE and Fe is present surrounding the main phase, and the RE2Fe 14 The metal structure with a fine single magnetic domain critical diameter of the B-type tetragonal compound leads to a decrease in magnetic properties in the same manner as when the temperature is less than 10°C / second. Therefore, the heating rate is preferably 10°C / second or more and less than 200°C / second, more preferably 30°C / second to 200°C / second, and further preferably 40°C / second to 180°C / second.
[0082] In the flash annealing (crystallization heat treatment) of the manufacturing method of the iron-based rare earth boron isotropic nanocomposite magnet alloy of the present invention, in order to obtain good magnetic properties, it is preferred to immediately perform rapid cooling after reaching the crystallization heat treatment temperature (holding temperature) in a certain temperature range above the crystallization temperature and below 850°C. Specifically, it is sufficient to hold the temperature from the above-mentioned crystallization heat treatment temperature until rapid cooling for substantially more than 0.1 seconds. If it is held for more than 7 minutes, the uniform and fine metal structure will be damaged, resulting in a decrease in various magnetic properties, so it is not preferred. Therefore, the holding time is preferably more than 0.1 seconds and less than 7 minutes, more preferably 0.1 seconds to 2 minutes, and further preferably 0.1 seconds to 30 seconds.
[0083] In the flash annealing (crystallization heat treatment) of the method for manufacturing the iron-based rare earth boron isotropic nanocomposite magnet alloy of the present invention, it is preferred to cool the quenched solidified alloy to below 400°C at a cooling rate of 2°C / sec to 200°C / sec. If the cooling rate is less than 2°C / sec, the coarsening of the crystal structure proceeds, and when it exceeds 200°C / sec, the alloy may oxidize. Therefore, the cooling rate is preferably 2°C / sec to 200°C / sec, more preferably 5°C / sec to 200°C / sec, and further preferably 5°C / sec to 150°C / sec.
[0084] In order to prevent oxidation of the rapidly solidified alloy, the atmosphere of the above-mentioned flash annealing (crystallization heat treatment) is preferably an inert gas atmosphere. As the inert gas, rare gases such as helium and argon, and nitrogen can be used, but nitrogen is more likely to react with rare earth elements and iron, so rare gases such as helium and argon are preferred, and argon is more preferred from the cost point of view.
[0085] [Crushing and molding]
[0086] The method for producing powder composed of the iron-based rare earth boron isotropic nanocomposite magnet alloy of the present invention may further include the following step: pulverizing the above-mentioned rapidly solidified alloy or the above-mentioned rapidly solidified alloy subjected to the above-mentioned flash annealing to produce the iron-based rare earth boron isotropic nanocomposite magnet alloy powder.
[0087] The rapidly solidified alloy obtained through the above process can be roughly cut or crushed into a thin strip of the rapidly solidified alloy before flash annealing (crystallization heat treatment) to, for example, less than 50 mm. In addition, by crushing the magnet alloy of the present invention after flash annealing (crystallization heat treatment) into a magnet alloy powder with an appropriate average powder particle size in the range of 20 μm to 200 μm, the magnet alloy powder can be used to manufacture various resin-bonded permanent magnets (commonly known as plastic magnets or bonded magnets) through known processes.
[0088] The manufacturing method of the resin-bonded permanent magnet of the present invention may include the following steps: a step of preparing an iron-based rare earth boron isotropic nanocomposite magnet alloy powder manufactured by the above-mentioned method of manufacturing an iron-based rare earth boron isotropic nanocomposite magnet alloy, and a step of adding a thermosetting resin to the above-mentioned iron-based rare earth boron isotropic nanocomposite magnet alloy powder, filling it into a molding mold, and performing heat treatment above the polymerization temperature of the above-mentioned thermosetting resin after forming a compression molded body through compression molding.
[0089] The manufacturing method of the resin-bonded permanent magnet of the present invention may include the following steps: a step of preparing an iron-based rare earth boron isotropic nanocomposite magnet alloy powder manufactured by the above-mentioned method of manufacturing an iron-based rare earth boron isotropic nanocomposite magnet alloy, and a step of adding a thermoplastic resin to the above-mentioned iron-based rare earth boron isotropic nanocomposite magnet alloy powder to prepare a composite material for injection molding, and then performing injection molding.
[0090] When making the above-mentioned resin-bonded permanent magnet, iron-based rare earth nanocomposite magnet powder is mixed with epoxy resin, polyamide, polyphenylene sulfide (PPS), liquid crystal polymer, acrylic acid, polyether, etc., and molded into a desired shape. At this time, for example, mixed magnet powder mixed with permanent magnet powders such as SmFeN magnet powder and hard ferrite magnet powder can be used.
[0091] By using the above-mentioned resin-bonded permanent magnet, it is possible to manufacture a brushless DC motor that is required to be compact and heat-resistant, such as various electric motors for EVs and HEVs.
[0092] When the magnet alloy powder of the present invention is used for injection molding bonded magnets, it is preferably crushed to an average particle size of 100 μm or less, and the more preferred average crystal particle size of the powder is 20 μm to 100 μm. In addition, when used for compression molding bonded magnets, it is preferably crushed to an average particle size of 200 μm or less, and the more preferred average crystal particle size of the powder is 50 μm to 150 μm. It is further preferred that the particle size distribution has two peaks and the average crystal particle size is 80 μm to 130 μm.
[0093] It should be noted that by subjecting the surface of the magnet alloy powder of the present invention to surface treatments such as coupling treatment and chemical conversion treatment (including phosphoric acid treatment and glass film treatment), the moldability of the resin-bonded permanent magnet during molding, the corrosion resistance and heat resistance of the obtained resin-bonded permanent magnet can be improved regardless of the molding method. In addition, the surface of the resin-bonded permanent magnet after molding is subjected to surface treatments such as resin coating, chemical conversion treatment, and plating, which can also improve the corrosion resistance and heat resistance of the resin-bonded permanent magnet in the same way as the surface treatment of the magnet alloy powder.
[0094] It should be noted that the method for manufacturing the iron-based rare earth boron isotropic nanocomposite magnet alloy of the present invention is not limited to the above method, and other manufacturing methods may be used as long as the iron-based rare earth boron isotropic magnet alloy having the above composition, average crystal grain size, etc. can be manufactured. For example, if flash annealing is used, RE2Fe with an average crystal grain size of 10 nm or more and less than 70 nm can be formed. 14 The fine metal structure with B-type tetragonal compound as the main phase, but the formation of such a fine metal structure is not limited to flash annealing, and other methods can also be used. For example, even when a normal annealing process is used instead of flash annealing, the surface speed of the rotating roller that rapidly cools the alloy melt is adjusted to make the rapidly solidified alloy structure into a homogeneous fine metal structure composed of crystal grains about 5% to 20% smaller than the alloy structure that obtains the best magnetic properties. Good magnetic properties can also be obtained.
[0095] Example
[0096] Hereinafter, examples of the present invention will be described, but it should be noted that the present invention is not limited to these examples.
[0097] (Example)
[0098] 100 g of a billet containing main elements of Nd, Pr, B, Co, C, Zr and Fe with a purity of 99.5% or more and additional elements such as Si, Ti, Cu, Zn, Ga, Nb and Hf was placed in an alumina melting crucible and placed on a working coil in a vacuum melting furnace so as to obtain the alloy composition described in Table 1. Then, the vacuum melting furnace was evacuated to 0.02 Pa or less, argon gas was introduced to normal pressure, and alloy melt was prepared by high-frequency induction heating. Thereafter, the alloy melt was cast into a water-cooled copper mold to prepare a master alloy.
[0099] Next, the obtained master alloy was cut into appropriate sizes, and 40 g was inserted into a transparent quartz nozzle having orifices of different diameters (0.7 mm to 1.2 mm) appropriately arranged at the bottom in a manner to achieve the average discharge rate recorded in Table 1 (simply indicated as "discharge rate" in Table 1), and then placed on a working coil in a single-roll quenching device. Then, after the vacuum melting furnace was evacuated to below 0.02 Pa, argon gas was introduced until the quenching atmosphere pressure recorded in Table 1, and the master alloy was re-melted by high-frequency induction heating. The alloy melt was discharged from the nozzle orifice at a spray pressure of 30 kPa onto the surface of a rotating roller rotating at the roller surface speed (Vs) recorded in Table 1 to produce a quenched solidified alloy. It should be noted that at this time, the distance between the nozzle tip and the rotating roller surface was 0.8 mm. In addition, the main component of the rotating roller is copper. In addition, the obtained quenched solidified alloy has a content of Nd2Fe of more than 1 volume %. 14 The B phase is either a crystalline phase or an amorphous phase.
[0100] Figure 4 The powder X-ray diffraction pattern of the rapidly solidified alloy obtained in Example 9 is shown in FIG. Figure 4 It was confirmed that Nd2Fe existed in the quenched solidification state. 14 B.
[0101] The rapidly solidified alloy obtained in the above process is coarsely crushed to less than a few mm to prepare a rapidly solidified alloy powder. Then, a flash annealing furnace (crystallization heat treatment furnace, furnace core tube: made of transparent quartz and with an outer diameter of 15 mm × an inner diameter of 12.5 mm × a length of 1000 mm, a heating area of 300 mm, and a cooling area of 500 mm for the cooling fan) is used to put the coarse powder of the rapidly solidified alloy into a raw material hopper, and then heat treatment is carried out at a workpiece cutting speed of 20 g / min. It should be noted that the inclination angle of the furnace core tube, the rotation speed of the furnace core tube, and the vibration frequency of the furnace core tube are appropriately adjusted together with the heat treatment temperature and heat treatment time recorded in Table 2 in a manner to obtain the heating rate recorded in Table 2. As a result, the rapidly solidified alloy powder passes through the furnace core tube while undergoing a combination of stirring based on the rotational motion of the furnace core tube and jumping phenomena based on the vibration of the furnace core tube, so that the rapidly solidified alloy powder is placed under specific heat treatment conditions in which each powder is subjected to a heat history instead of being subjected to a heat history as a whole. The heat treatment furnace and the heat history in the flash annealing process are respectively Figure 2 and Figure 3 An example is shown in FIG.
[0102] The phase composition of the rapidly solidified alloy powder after flash annealing (crystallization heat treatment) was confirmed by powder X-ray diffraction. 14 B phase and Fe 17 The presence of RE2 phase. Figure 5 The powder X-ray diffraction pattern of the rapidly solidified alloy obtained in Example 9 after flash annealing (crystallization heat treatment) is shown as a representative example. Figure 4 Fe not seen in 17 The peak of RE2 phase after flash annealing (crystallization heat treatment) Figure 5 It is confirmed to be Nd2Fe 14 B phase and Fe 17 A composite structure in which RE2 phases coexist. In addition, element mapping using TEM-EDX was performed on the flash annealed (crystallization heat treatment) rapidly cooled alloy obtained in Example 24, and the presence of a phase richer in Fe than the main phase was confirmed. Figure 6 The element mapping image obtained in Example 24 is shown as a representative example. Figure 6 The left image is a bright field STEM image, where the main phase and grain boundary phase can be identified. Figure 6 The right figure is a mapping image of Fe, and it can be confirmed that Fe is rich in the position corresponding to the grain boundary in the left figure.
[0103] By observing the bright field image and element mapping of the rapidly solidified alloy subjected to flash annealing (crystallization heat treatment) with a transmission electron microscope, the presence of Nd2Fe2O3 with an average crystal grain size of less than 50 nm was confirmed in the bright field image. 14 B phase and surrounding Nd2Fe 14In addition, element mapping confirmed the presence of a grain boundary phase where Nd and Fe were concentrated at the grain boundary of the main phase composed of Nd, Fe, and B as the main constituent elements. Based on the above powder X-ray diffraction results, it is speculated that there is a grain boundary phase containing Fe. 17 The grain boundary of the RE2 phase composed of Fe and RE. It should be noted that the present inventors confirmed that a grain boundary containing Fe was formed in all the examples. 17 The grain boundary phase of the RE2 phase is composed of Fe and RE. In addition, in all embodiments, the width of the thickest part of the grain boundary phase is greater than 1nm and less than 150nm. For example, in the grain boundary phase observed in Example 24, various thicknesses are mixed, but the width of the thickest part is 2nm to 117nm. In addition, in all embodiments, in the composition ratio of the main phase to the grain boundary phase, the ratio of the main phase is greater than 70 volume% and less than 99 volume%, and the ratio of the grain boundary phase is greater than 1 volume% and less than 30 volume%. For example, in Example 1, in the composition ratio of the main phase to the grain boundary phase, the ratio of the grain boundary phase is 18 volume%, and the ratio of the main phase is 82 volume%.
[0104] The iron-based rare earth boron isotropic magnet alloy obtained by flash annealing (crystallization heat treatment) described in Table 2 was made into a sample for magnetic property evaluation with a length of about 7 mm × a width of about 0.9 mm to 2.3 mm × a thickness of 18 μm to 25 μm, and then magnetized in the long side direction with a pulsed magnetic field of 3.2 MA / m. Thereafter, in order to suppress the influence of the demagnetization field, the sample for magnetic property evaluation was set in the long side direction, and then the room temperature magnetic properties were measured using a vibrating sample magnetometer (VSM), and the results are shown in Table 3. It can be seen from Table 3 that the above-mentioned residual magnetic flux density Br obtained by the alloy composition and preparation method described in Examples 1 to 24 is greater than or equal to 0.81 T, the inherent coercive force HcJ is greater than or equal to 1200 kA / m and less than 1700 kA / m, and the maximum energy product (BH) max is 110 kJ / m 3 The above magnetic properties.
[0105] Next, the flash annealed (crystallization heat treated) magnetic powder obtained in Example 9 was crushed into an average particle size of 125 μm using a pin mill. Then, 2% by mass of epoxy resin diluted with methyl ethyl ketone (MEK) was added to the crushed magnetic powder, mixed and kneaded, and 0.1% by mass of calcium stearate was added as a lubricant to prepare a composite for compression molding bonded magnets.
[0106] The above-mentioned compression molded bonded magnet composite was heated to 1568 MPa (16 ton / cm 2) pressure to obtain a compression molded body with a diameter of 10 mm × height of 7 mm, and then subject the compression molded body to a curing heat treatment (curing) at 180°C × 1 hour in an argon atmosphere, thereby obtaining an isotropic compression molded bonded magnet. It should be noted that the obtained isotropic compression molded bonded magnet has a molded body density of 6.3 g / cm 3 (The true specific gravity of magnetic powder is 7.5g / cm 3 ), and the magnetic powder filling rate is 84 volume %.
[0107] The magnetic properties of the isotropic compression molded bonded magnet obtained by using the magnetic powder of Example 9 were measured by a BH tracer after magnetization in the long side direction with a pulsed magnetic field of 3.2MA / m. The results showed that the residual magnetic flux density Br: 0.71T, the inherent coercive force HcJ: 1223kA / m, and the maximum energy product (BH) max: 82.2kJ / m 3 Magnetic properties.
[0108] Next, the flash annealed (crystallization heat treated) magnetic powder obtained in Example 9 was crushed into an average particle size of 75 μm using a pin mill. Then, the crushed magnetic powder was heated and stirred while spraying 0.75% by mass of a titanate coupling agent, and after the coupling treatment, 0.5% by mass of stearic acid amide and 4.75% by mass of nylon 12 resin powder as a lubricant were added and mixed, and then a continuous extruder was used to prepare a composite for injection molding bonded magnets at an extrusion temperature of 170°C.
[0109] The above-mentioned compound for injection molding bonded magnet was injection molded at an injection temperature of 250°C to produce an isotropic injection molded bonded magnet having a shape of 10 mm in diameter and 7 mm in height. The obtained isotropic injection molded bonded magnet had a molded body density of 4.6 g / cm 3 (The true specific gravity of magnetic powder is 7.5g / cm 3 ), so the magnetic powder filling rate is 61 volume %.
[0110] The magnetic properties of the isotropic injection molded bonded magnet obtained by using the magnetic powder of Example 9 were measured by a BH tracer after magnetization in the long side direction by applying a pulse magnetic field of 3.2MA / m. The results showed that the residual magnetic flux density Br: 0.51T, the inherent coercive force HcJ: 1218kA / m, and the maximum energy product (BH) max: 60.1kJ / m 3 The magnetic properties of the magnets are comparable to those of commonly used isotropic Nd-Fe-B compression molded bonded magnets even when injection molded.
[0111] (Comparative Example)
[0112] 100 g of a billet containing main elements of Nd, Pr, Dy, B and Fe with a purity of 99.5% or more and additive elements such as Co and Nb was placed in an alumina melting crucible so as to obtain the alloy composition described in Table 1, and then placed in a working coil in a vacuum melting furnace. Then, the vacuum melting furnace was evacuated to 0.02 Pa or less, and argon gas was introduced until it reached normal pressure, and then alloy melt was prepared by high-frequency induction heating. Thereafter, the alloy melt was cast into a water-cooled copper mold to prepare a master alloy.
[0113] Next, the obtained master alloy was cut into appropriate sizes, and 40 g was inserted into a transparent quartz nozzle having orifices of different diameters (0.7 mm to 1.2 mm) appropriately arranged at the bottom so as to achieve the average discharge rate listed in Table 1 (simply indicated as "discharge rate" in Table 1), and then placed in a working coil in a single-roll quenching device. Then, after the vacuum melting furnace was evacuated to 0.02 Pa or less, argon gas was introduced until the quenching atmosphere pressure listed in Table 1, and the master alloy was re-melted by high-frequency induction heating, and the alloy melt was discharged from the nozzle hole at a spray pressure of 30 kPa onto the surface of a rotating roller rotating at the roller surface speed (Vs) listed in Table 1 to produce a quenched solidified alloy. It should be noted that at this time, the distance between the nozzle tip and the rotating roller surface was 0.8 mm.
[0114] The rapidly solidified alloy obtained in the above process was coarsely crushed to a few mm or less to make a rapidly solidified alloy powder, and then the coarse powder of the rapidly solidified alloy was put into the raw material hopper using a flash annealing furnace (crystallization heat treatment furnace, furnace core tube: transparent quartz and outer diameter 15mm×inner diameter 12.5mm×length 1000mm, heating area 300mm, cooling area 500mm of the cooling fan), and then heat treated at a workpiece cutting speed of 20g / min. It should be noted that the furnace core tube inclination angle, furnace core tube rotation speed and furnace core tube vibration frequency were appropriately adjusted together with the heat treatment temperature and heat treatment time recorded in Table 2 in a manner that the heating rate recorded in Table 2 is obtained.
[0115] The phase composition of the rapidly solidified alloy powder after flash annealing (crystallization heat treatment) was confirmed by powder X-ray diffraction, and the presence of Nd2Fe 14 Phase B. Figure 7 The powder X-ray diffraction pattern of the rapidly solidified alloy obtained in Comparative Example 7 after flash annealing (crystallization heat treatment) is shown as a representative example. Figure 7 , confirming that Comparative Example 7 is Nd2Fe 14 A single-phase metal structure with phase B as the main phase.
[0116] By observing the bright field image and element mapping of the iron-based rare earth boron-based isotropic magnet alloy obtained in Comparative Example 7 with a transmission electron microscope, it can be confirmed in the bright field image that Nd2Fe 14 B phase, but no clear grain boundary phase can be confirmed. In addition, element mapping also shows that there is no grain boundary phase in which Fe and RE are concentrated as seen in Example 9 at the crystal grain boundary of the main phase composed of the main constituent elements of Nd, Fe, and B. This is also the case in other comparative examples.
[0117] The iron-based rare earth boron isotropic magnet alloy obtained by flash annealing (crystallization heat treatment) described in Table 2 was made into a sample for magnetic property evaluation with a length of about 7 mm × a width of about 0.9 mm to 2.3 mm × a thickness of 18 μm to 25 μm, and then magnetized in the long side direction with a pulsed magnetic field of 3.2 MA / m. Thereafter, in order to suppress the influence of the demagnetization field, the sample for magnetic property evaluation was set in the long side direction, and the room temperature magnetic properties were measured by a vibrating sample magnetometer (VSM), and the results are shown in Table 3. As can be seen from Table 3, the above-mentioned Br: 0.81T or more, HcJ: 1200 kA / m or more and less than 1700 kA / m, (BH)max: 110 kJ / m cannot be obtained by the alloy composition and preparation method described in Comparative Examples 1 to 12. 3 The above magnetic properties.
[0118] Generally speaking, the residual magnetic flux density Br and the intrinsic coercive force HcJ are in a trade-off relationship, and it is difficult to achieve both high residual magnetic flux density Br and high intrinsic coercive force HcJ. In contrast, in this embodiment, by having an Fe-rich grain boundary phase with a width of the thickest part of the grain boundary phase of more than 1nm and less than 150nm as described above, it is possible to effectively exert exchange interaction between the main phase and the grain boundary phase, thereby improving the characteristics of both. For example, in Example 11 and Comparative Example 5, although they have the same degree of high intrinsic coercive force HcJ, Example 11 achieves a residual magnetic flux density Br higher than Comparative Example 5.
[0119] [Table 1]
[0120]
[0121] [Table 2]
[0122]
[0123] [Table 3]
[0124]
[0125] Explanation of symbols
[0126] 1Raw material hopper
[0127] 2Raw material supply feeder
[0128] 3 Furnace core tube
[0129] 3a Enlarged view of furnace core tube
[0130] 3b Enlarged view of the cross section of the furnace core tube
[0131] 4 Tubular furnace
[0132] 5Cooling Tower
[0133] 6. Recovery hopper
[0134] 7 Vibrator
[0135] 8 Furnace core tube rotation motor
[0136] 9 Furnace core tube rotation axis
[0137] 10 device racks
[0138] 11 Furnace core tube tilt angle
[0139] 12 Cooling fan wind
[0140] 13 Rapidly solidified alloy powder (workpiece)
[0141] 14 Workpiece moving direction
[0142] 15 Workpiece jumping phenomenon
[0143] 16 Heating speed
[0144] 17. Maintain Temperature
[0145] 18 Cooling speed
[0146] 21 Main Phase
[0147] 22 Grain boundary phase
Claims
1. An iron-based rare earth boron isotropic nanocomposite magnet alloy, characterized in that: The alloy composition is as follows: Having the composition formula T 100-x-y-z (B 1-n C n ) x RE y Zr z M m It represents that T is at least one element selected from Fe, Co and Ni and is a transition metal element that must contain Fe, RE is at least one rare earth element of Nd and Pr that must contain Nd, M is one or more metal elements selected from Al, Si, V, Cr, Ti, Mn, Cu, Zn, Ga, Nb, Mo, Ag, Hf, Ta, W, Pt, Au and Pb, and the composition ratios x, y and z respectively satisfy 4.2 atomic % ≤ x ≤ 5.0 atomic %, 12.5 atomic % ≤ y ≤ 14.0 atomic %, 0 atomic % < z ≤ 2.0 atomic %, 0.5 atomic % ≤ m ≤ 5.0 atomic % and 0.0 ≤ n ≤ 0.5; Moreover, B contains a concentration lower than RE2Fe 14 The stoichiometric composition of the B-type tetragonal compound and the RE2Fe2O3 having an average crystal particle size of 10 nm or more and less than 70 nm which is finer than the single magnetic domain critical diameter 14 The B-type tetragonal compound is a main phase, and a phase richer in Fe than the main phase is included in a grain boundary phase surrounding the main phase.
2. The iron-based rare earth boron isotropic nanocomposite magnet alloy according to claim 1, wherein: The width of the thickest portion of the grain boundary phase is greater than or equal to 1 nm and less than 150 nm.
3. The iron-based rare earth boron isotropic nanocomposite magnet alloy according to claim 1 or 2, wherein: In the composition ratio of the main phase to the grain boundary phase, the ratio of the main phase is 70 volume % or more and less than 99 volume %, and the ratio of the grain boundary phase is 1 volume % or more and less than 30 volume %.
4. The iron-based rare earth boron isotropic nanocomposite magnet alloy according to any one of claims 1 to 3, which exhibits a residual magnetic flux density Br of 0.81T or more, an intrinsic coercive force HcJ of 1200kA / m or more and less than 1700kA / m, and a maximum energy product (BH)max of 110kJ / m 3 The above magnetic properties.
5. The iron-based rare earth boron-based isotropic nanocomposite magnet alloy according to any one of claims 1 to 4, wherein: The RE contains at least Nd and Pr.
6. A method for manufacturing an iron-based rare earth boron isotropic nanocomposite magnet alloy, comprising the following steps: A step of preparing an alloy melt having a composition represented by the composition formula T 100-x-y-z (B 1-n C n ) x RE y Zr z M m It indicates that, T is at least one element selected from Fe, Co and Ni and is a transition metal element that must contain Fe, RE is at least one rare earth element selected from Nd and Pr and must contain Nd, M is one or more metal elements selected from Al, Si, V, Cr, Ti, Mn, Cu, Zn, Ga, Nb, Mo, Ag, Hf, Ta, W, Pt, Au and Pb, and the composition ratios x, y and z respectively satisfy 4.2 atomic % ≤ x ≤ 5.0 atomic %, 12.5 atomic % ≤ y ≤ 14.0 atomic %, 0 atomic % < z ≤ 2.0 atomic %, 0.0 atomic % ≤ m ≤ 5.0 atomic % and 0.0 ≤ n ≤ 0.5; as well as The alloy melt is ejected onto the surface of a rotating roll mainly composed of Cu, Mo, W or an alloy containing at least one of these metals at an average discharge rate of 200 g / min or more and less than 2000 g / min per one of the orifices arranged at the front end of the nozzle, thereby producing a roll having 1 volume % or more of RE2Fe 14 A step of rapidly solidifying the alloy by quenching either the crystalline phase or the amorphous phase of the B phase.
7. The method for producing an isotropic iron-based rare earth boron-based nanocomposite magnet alloy according to claim 6, wherein: The method further comprises the step of performing flash annealing, namely, after the rapidly solidified alloy is heated to a certain temperature range of not less than the crystallization temperature and not more than 850° C. at a heating rate of not less than 10° C. / second and not more than 200° C. / second, the alloy is rapidly cooled after not less than 0.1 second and not more than 7 minutes. By implementing the flash annealing process, the following nanocomposite metal structure is formed: B contains a concentration lower than RE2Fe 14 The stoichiometric composition of the B-type tetragonal compound is RE2Fe with an average crystal particle size of 10 nm or more and less than 70 nm, which is finer than the single magnetic domain critical diameter. 14 The B-type tetragonal compound is a main phase, and a grain boundary phase surrounding the main phase contains a phase richer in Fe than the main phase.
8. A method for manufacturing a powder composed of the iron-based rare earth boron isotropic nanocomposite magnet alloy as described in claim 6 or 7, further comprising the following step: preparing the iron-based rare earth boron isotropic magnet alloy powder by crushing the rapidly solidified alloy or the rapidly solidified alloy subjected to the flash annealing.
9. A method for manufacturing a resin-bonded permanent magnet, comprising the following steps: A step of preparing an iron-based rare earth boron-based isotropic nanocomposite magnet alloy powder produced by the method for producing an iron-based rare earth boron-based isotropic nanocomposite magnet alloy according to claim 7 or 8, and A process of adding a thermosetting resin to the iron-based rare earth boron-based isotropic nanocomposite magnet alloy powder, filling it into a molding die, and then performing a compression molding process to form a compression molded body, followed by heat treatment at a temperature above the polymerization temperature of the thermosetting resin.
10. A method for manufacturing a resin-bonded permanent magnet, comprising the following steps: A step of preparing an iron-based rare earth boron-based isotropic nanocomposite magnet alloy powder produced by the method for producing an iron-based rare earth boron-based isotropic nanocomposite magnet alloy according to claim 7 or 8, and A thermoplastic resin is added to the iron-based rare earth boron-based isotropic nanocomposite magnet alloy powder to prepare a composite material for injection molding, and then an injection molding process is performed.
Citation Information
Patent Citations
Permanent magnet
JP1984046008A
High energy stored rare earth-iron magnetic alloy
JP1985009852A
Permanent magnet material, permanent magnet and manufacture of permanent magnet
JP1996162312A
(rare earth)-iron-boron magnetic alloy and its production and bond magnet using the (rare earth)-iron-boron magnetic alloy
JP1998053844A
Permanent magnet having plural ferromagnetic phases, and its manufacturing method
JP2002175908A